Mapping of N−C Bond Formation from a Series of Crystalline Peri‐Substituted Naphthalenes by Charge Density and Solid‐State NMR Methodologies. (1st October 2021) - Rees, Gregory J.; Pitak, Mateusz B.; Lari, Alberth; Day, Stephen P.; Yates, Jonathan R.; Gierth, Peter; Barnsley, Kristian; Smith, Mark E.; Coles, Simon J.; Hanna, John V.; Wallis, John D.
Abstract: A combination of charge density studies and solid state nuclear magnetic resonance (NMR) 1 J NC coupling measurements supported by periodic density functional theory (DFT) calculations is used to characterise the transition from an n–π* interaction to bond formation between a nucleophilic nitrogen atom and an electrophilic sp 2 carbon atom in a series of crystalline peri‐substituted naphthalenes. As the N⋅⋅⋅C distance reduces there is a sharp decrease in the Laplacian derived from increasing charge density between the two groups at ca. N⋅⋅⋅C = 1.8 Å, with the periodic DFT calculations predicting, and heteronuclear spin‐echo NMR measurements confirming, the 1 J NC couplings of ≈3–6 Hz for long C−N bonds (1.60–1.65 Å), and 1 J NC couplings of <1 Hz for N⋅⋅⋅C >2.1 Å. Abstract : A combination of charge density measurements, solid‐state NMR 1 J NC couplings, and DFT calculations is presented to characterise the transition from an n–π* interaction to bond formation for a series of model crystalline peri‐substituted naphthalenes.